Mapping the Landscape of MOOCs Research: A Bibliometric Analysis of Top 100 Cited Papers - Devi, Poornima; Preeti; Rani, Ritu; Kumar, Amit; Siwach, Anil Kumar (DESIDOC Journal of Library & Information Technology, 2025)
This study analysed the top 100 cited papers on MOOCs research to identify prolific contributors and factors influencing citation count. Bibliometric approach was employed to examine the objectives. Various aspects of the publications, such as publication year, accessibility, document type, research design, top contributors, collaboration patterns, and factors influencing citation count, were analysed. The study found that highly cited papers on MOOCs research from 2013 to 2016 consisted mainly of articles and conference papers. Open-access publications received more citations compared to subscription-based papers, and papers that applied a mixed method approach to research design received the highest average citation. The USA has produced the highest number of highly cited papers and R.F. Kizilcec, P.J. Guo, and J. Reich were the most prolific authors. This study aims to provide valuable insights to improve student engagement, retention rates, and access to education.